Portraying lives : headmistresses and women professors, 1880s-1940s - Fitzgerald, Tanya, 1960-; May, Josephine, 1950- (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The expansion of women's higher education in the late 19th and early 20th centuries in Australia and New Zealand offered educated women opportunities to broaden their aspirations, horizons and experiences across many professional fields. Engaged in the public activity of teaching in a range of educational institutions, women were able to exercise a level of professional expertise, authority and independence. Paradoxically, women were both empowered by the possibilities of educational careers yet at the same time restricted by the historical era in which they lived and the feminized positions they occupied. In this book, we draw on Sarah Lawrence-Lightfoot and Jessica Hoffmann Davis' methodological adoption of the use of portraits and portraiture to frame our history of women educators and highlight their unsettled acceptance of contemporary constraints and pressures exerted on educated women. This book will be essential reading for those involved or interested in the historiography of women's education, women teachers and headmistresses, women's higher education, educational biography and visual methodologies. This book will also be of particular relevance to those engaged in the study of history, sociology, women and gender studies, teacher education, educational research, and history of education.